Developing RESTful web services with Jersey 2.0 create RESTful web services smoothly using the robust Jersey 2.0 and JAX-RS APIs /: create RESTful web services smoothly using the robust Jersey 2.0 and JAX-RS APIs. (2013) - Unknown
No abstract available